To solve the system of equations:
- \( y = -3x + 4 \) (Equation 1)
- \( y + 3x = -4 \) (Equation 2)
We can substitute Equation 1 into Equation 2.
Starting with Equation 2:
\[ y + 3x = -4 \]
Substituting \( y \) from Equation 1:
\[ (-3x + 4) + 3x = -4 \]
Now, simplify the left side:
\[ -3x + 4 + 3x = -4 \]
The \( -3x \) and \( +3x \) cancel each other out:
\[ 4 = -4 \]
This statement is false, indicating that there is no solution to this system of equations. The lines represented by these equations are parallel and do not intersect.